Electrospinning-Driven Binary Oxide Nanofiber Networks with Tunable Amorphous Microstructure for Booming Transistors and Circuits Operation - He, Bo (2023)
Funding Information: This work was financially supported by the National Natural Science Foundation of China (Grant Nos. 11774001 and 52202156). The authors also acknowledge the support from Anhui Project (No.Z010118169), and the Open Fund Project of Zhejiang Engineering Research Center of MEMS in Shaoxing University (MEMSZJERC2202). Publisher Copyright: © 2023 The Authors. Advanced Electronic Materials published by Wiley-VCH GmbH.